Early and late complications of bariatric operation. Issue 1 (9th October 2018) - Lim, Robert; Beekley, Alec; Johnson, Dirk C; Davis, Kimberly A
Abstract : Weight loss surgery is one of the fastest growing segments of the surgical discipline. As with all medical procedures, postoperative complications will occur. Acute care surgeons need to be familiar with the common problems and their management. Although general surgical principles generally apply, diagnoses specific to the various bariatric operations must be considered. There are anatomic considerations which alter management priorities and options for these patients in many instances. These problems present both early or late in the postoperative course. Bariatric operations, in many instances, result in permanent alteration of a patient's anatomy, which can lead to complications at any time during the course of a patient's life. Acute care surgeons diagnosing surgical emergencies in postbariatric operation patients must be familiar with the type of surgery performed, as well as the common postbariatric surgical emergencies. In addition, surgeons must not overlook the common causes of an acute surgical abdomen—acute appendicitis, acute diverticulitis, acute pancreatitis, and gallstone disease—for these are still among the most common etiologies of abdominal pathology in these patients.